PENGARUH KUALITAS LAYANAN DAN SISTEM ADMINISTRASI PERPAJAKAN ELEKTRONIK TERHADAP KEPATUHAN WAJIB PAJAK BADAN KPP PRATAMA PASURUAN MELALUI KEPUASAN WAJIB PAJAK SEBAGAI VARIABEL PENGHUBUNG - Islam, Saiful; Martaleni, Martaleni; Astuti, Rini (Magister Manajemen Universitas Wisnuwardhana, 2020)
High level of taxpayer compliance is one of the keys to success in achieving tax revenue targets. To improve taxpayer compliance, the Directorate General of Taxes has made several efforts including improving service quality and implementing an electronic tax administration system. The research objective is to determine the magnitude of the effect of service quality and electronic tax administration system on taxpayer compliance which is mediated by taxpayer satisfaction. Data collection by distributing questionnaires to 94 taxpayers as research samples. Statistical analysis used was a path analysis system that was processed with SPSS Version 18. The results of this research stated that service quality directly did not have a significant effect on taxpayer compliance, but indirectly through taxpayer satisfaction service quality significantly affected mandatory compliance tax. While the electronic tax administration system directly has a significant effect on taxpayer compliance but indirectly through taxpayer satisfaction does not have a significant effect on taxpayer compliance. Keywords: Service quality, Electronic Tax Administration System, Satisfaction, and Taxpayer Compliance